Research and Design of Durability of High PerformanceAnti-abrasion Concrete in Dry Environment - HU Hongxia (Renmin Zhujiang)
For the water conservancy and hydropower anti-abrasion concrete in dry environment, dueto the low water-binder ratio, the durability problems such as concrete shrinkage cracking andvoid are very prominent, and the cost of maintenance and repair is huge. For this reason, combinedwith a mix design test project, and based on moderate heat cement mixed with fly ash and silicapowder, polypropylene fiber, polycarboxylic acid water reducing agent and shrinkage reducingagentare added to modify the concrete. The results show that compared with naphthalene waterreducer, for concrete with polycarboxylic acid water reducing agent, the dry shrinkage rate isreduced by 13%, and the crack width is reduced by 76%;for concrete with polypropylene fiber, thecrack width is reduced by 65%;while for concrete with shrinkage reducing agent, the dry shrinkagerate is reduced by about 30%, and the crack width is reduced by 34%. In view of thecharacteristics of high dry shrinkage of anti-abrasion concrete in dry environment, it issuggested to adopt the technical scheme of polycarboxylic acid water reducing agent added withpolypropylene fiber and shrinkage reducing agent for mix design, so as to better solve thedurability problems such as shrinkage, cracking and void of anti-abrasion concrete.